Neurologic manifestations of E coli infection-induced hemolytic-uremic syndrome in adults - Weissenborn, Karin; Donnerstag, Frank; Kielstein, Jan T.; Heeren, Meike; Worthmann, Hans; Hecker, Hartmut; Schmitt, Roland; Schiffer, Mario; Pasedag, Thomas; Schuppner, Ramona; Tryc, Anita B.; Raab, Peter; et al. (Neurology, 2012)
Objective: To describe the neurologic and neuroradiologic complications of Shiga toxin producing Escherichia coli infection (STEC)-associated hemolytic-uremic syndrome (HUS) in adults. Methods: All 52 adult patients with STEC O104:H4 infection cared for at Hannover Medical School during the outbreak in Germany through May-July 2011 are considered in this observational study. Forty-three of the 52 patients underwent a standard neurologic diagnostic procedure including clinical examination, Mini-Mental State Examination, and Glasgow Coma Scale Score. Thirty-six patients underwent EEG, and 26 had cerebral MRI, 9 of them repeatedly. Case records of 9 patients who had not been seen by a neurologist were analyzed retrospectively. Results: Forty-eight of the 52 patients had HUS. All but 1 of these showed neurologic symptoms. Focal neurologic signs like double vision, difficulties in finding words, or hyperreflexia were present in 23, additional deficits in orientation, attention, memory, or constructive abilities in 9, and marked impairment of consciousness in 15. MRI showed brainstem, midbrain, thalamus, corpus callosum, and white matter lesions in half of the patients, predominantly in diffusion-weighted images. The extent of MRI lesions did not correlate with clinical symptoms. General slowing but no focal alteration was found in half of the patients examined by EEG. Conclusion: Our findings suggest a toxic-metabolic pathology behind the neurologic impairment instead of multiple infarction due to microthrombosis. Future studies should aim to clarify if early antibiotic therapy or bowel cleansing might help to decrease the rate of neurologic complications in STEC-HUS. © 2012 by AAN Enterprises, Inc.
CRIS-Team Scopus Importer:2020-11-12